Analisis Hukum Tentang Kedudukan Anak Angkat dalam Kewarisan Menurut Hukum Perdata (Studi Putusan No. 32/Pdt.G/2022/PN Mks) - Resdianto Willem; Nurmiati; Haeriyah (Pledoi Law Jurnal, 2024)
ABSTRACT: A child is a responsibility that gives him respect and value as an individual. Adopting a child is the best option for families who have not yet been blessed with children, from the perspective of a legal state, "adopted child" and "legal procedure" are synonyms. Adopted children have the right to inherit their adoptive parents' assets in accordance with the Legitimacy as long as it does not harm other heirs. Regulated in Article 852 of the Civil Code, adopted children have the right to inherit the assets left behind by their adoptive parents in dealing with inheritance cases. This legitimacy depends on whether the child's adoption was carried out based on a court order or not. A judge is responsible for resolving civil disputes in court whose mission is to determine the applicable law. To determine a law, it is not enough for a judge to just examine the law, because it is possible that the law does not regulate it completely and unequivocally; Therefore, judges must investigate the values and norms that are common and prevailing in society. ABSTRAK: Seorang anak adaIah tanggung jawab yang memberinya rasa hormat dan niIai sebagai individu. Mengadopsi anak adaIah piIihan terbaik bagi keIuarga yang beIum dikaruniai anak, dari perspektif negara hukum, "anak angkat" dan "acara hukum" adaIah sinonim. Anak angkat berhak mewaris harta orang tua angkatnya sesuai dengan Legitieme seIama tidak merugikan ahIi waris Iainnya. Diatur daIam PasaI 852 KUH Perdata, anak angkat berhak mewarisi harta peninggaIan orang tua angkatnya daIam mengurus perkara waris. Legitimasi ini tergantung pada apakah pengangkatan anak itu diIakukan atas perintah pengadiIan atau tidak. Seorang hakim bertanggung jawab untuk menyeIesaikan sengketa perdata di pengadiIan yang misinya adaIah menentukan hukum yang berIaku. Untuk menetapkan suatu undang-undang, seorang hakim tidak cukup hanya memeriksa undang-undang, karena ada kemungkinan undang-undang tersebut tidak mengatur secara Iengkap dan tegas; oIeh karena itu, hakim harus menyeIidiki niIai serta norma yang Iazim dan berIaku daIam masyarakat.